Effects of Chinese herbal formula Erxian decoction for treating osteoporosis: a systematic review - Li J (Dove Medical Press, 2017)
Jin-Yu Li,1,* Yu-Song Jia,1,* Li-Min Chai,1 Xiao-Hong Mu,1 Sheng Ma,1 Lin Xu,1 Xu Wei21Department of Orthopaedics, Dongzhimen Hospital, Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 2Department of Scientific Research, Wangjing Hospital, China Academy of Chinese Medical Sciences, Beijing, People’s Republic of China *These authors contributed equally to this workPurpose: The aim is to systematically assess the effectiveness and safety of Chinese herbal formula Erxian decoction (EXD) for treating osteoporosis. Materials and methods: Six databases were searched from inception through September 17, 2016, without language restriction. All randomized controlled trials of EXD for osteoporosis were included. One or more outcome measures including fracture, change in bone mineral density (BMD), pain symptom improvement, bone biochemical markers, quality of life, adverse event or adverse drug reaction were evaluated. Study selection, data extraction, quality assessment, and data analyses were conducted according to Cochrane standards. Results: Eight trials including 644 patients investigated the effects of EXD in the treatment of osteoporosis. The methodological quality of the included trials was generally low. The meta-analysis from two trials showed favorable effects of EXD in improving BMD of lumbar spine (mean difference [MD]: 0.05 [0.03, 0.06]; I2=0%; P<0.00001) and BMD of femoral great trochanter (MD: 0.06 [0.02, 0.10]; I2=59%; P=0.005) compared with caltrate tablets. The other meta-analysis from two trials showed beneficial effects of EXD plus caltrate tablets and calcitriol in improving BMD of femoral neck (MD: 0.04 [0.00, 0.09]; I2=56%; P=0.04), the level of calcium (MD: 0.20 [0.15, 0.24]; I2=0%; P<0.00001), and phosphorus (MD: −0.28 [−0.39, −0.17]; I2=68%; P<0.00001) compared with caltrate tablets and calcitriol alone. The adverse drug reactions of EXD were mainly slight gastrointestinal symptoms.Conclusion: The study provides suggestive evidence of the superiority of EXD monotherapy or combination therapy over basic supplements for treating osteoporosis. However, the evidence remains weak. More rigorously designed and measured, randomized double-blind, placebo-controlled trials with larger sample size are needed to verify the current conclusions.Keywords: Chinese herbal formula, Erxian decoction, osteoporosis, systematic review, meta-analysis